2020
DOI: 10.1021/acsami.0c03527
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Interface Structures of M23C6 carbides at Grain Boundary in an Aged 100Mn13 High Carbon High Manganese Steel

Abstract: Multiple interface structures of M23C6 carbides precipitated at grain boundary in 100Mn13 high carbon high manganese steel, including the interface between the carbide particle and the matrix together with the interface between two adjacent carbides, were studied after 1050 °C solution treatment and subsequently after 475 °C aging treatment by high resolution transmission electron microscope (HRTEM) based on traditional transmission electron microscope (TEM). A growth model describing the adjacent M23C6 precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In that region, carbides mainly formed in the grain boundaries of austenite ( Figure 1 in supplementary materials ). It was reported in literature that M 23 C 6 carbide precipitating at austenite grain boundaries usually possesses coherent interface and orientation relationship with the austenite grain from which it precipitates [53][54][55][56] . So, the increase of the residual stress in the zone between the center of the sample and 180 µm could be justified by the increase of the amount of M 23 C 6 precipitates in grain boundaries.…”
Section: Residual Stress In Austenitementioning
confidence: 99%
See 1 more Smart Citation
“…In that region, carbides mainly formed in the grain boundaries of austenite ( Figure 1 in supplementary materials ). It was reported in literature that M 23 C 6 carbide precipitating at austenite grain boundaries usually possesses coherent interface and orientation relationship with the austenite grain from which it precipitates [53][54][55][56] . So, the increase of the residual stress in the zone between the center of the sample and 180 µm could be justified by the increase of the amount of M 23 C 6 precipitates in grain boundaries.…”
Section: Residual Stress In Austenitementioning
confidence: 99%
“…That residual stresses relaxation could be explained by a loss of coherency between the austenite matrix and the M 23 C 6 precipitates which resulted in a drop of the elastic energy and, as a consequence, a decrease of the residual stresses. Wen et al [55] and Ding et al [53] reported that M 23 C 6 starts precipitation at the grain boundary from an austenite grain with which it is in coherence then, grows fast into the interior of an adjacent grain without coherency forming curved incoherent interfaces. The same growth morphology was observed in the studied carburized samples.…”
Section: Residual Stress In Austenitementioning
confidence: 99%
“…Figure 5b,c are TEM images and electron diffraction patterns of the twin. The diffraction electrons of the HR3C twin exhibit the following three characteristics: first, the diffraction spots are neatly arranged on the electron layer line; second, diffraction spots appear individually in the 0th layer; third, the diffraction spots of the ±1 layer and ±2 layer appear in pairs [30]. Figure 5d-f show that polygonal particles with a length of about 300-400 nm were distributed in the crystal, and the electron diffraction pattern and EDS experiment results showed that they were NbCrN nitrides with simple tetragonal structure.…”
Section: Evolution Of Precipitated Phase Of Hr3c Steelmentioning
confidence: 99%
“…Introducing the interfacial phase is a promising way to enhance the interfacial characteristics of metal matrix composites. Nai et al reported the use of a nanoscale nickel (Ni) coating on the carbon nanotube (CNT) to enhance the interfacial characteristics in CNT-reinforced Mg composites . It was found that Ni-coated CNT resulted in Mg 2 Ni intermetallics forming on the interface, which led to simultaneous enhancements of the ultimate tensile strength and 0.2% yield strength by 45 and 75% for the Mg–Ni/CNT composites comparing with those of the Mg–CNT composites.…”
Section: Introductionmentioning
confidence: 99%